Apolipoprotein E genotype is associated with island sign in lobar intracerebral hemorrhage - Qiong Yang; Haixin Sun; Haixin Sun; Xinran Ma; Lu Tang; Xiaolu Liu; Xin Huang; Xiao Huang; Yong Chen; Danyang Tian; Xiangzhu Zeng; Nan Li; et al. (Frontiers in Neurology)
BackgroundThe island sign is a predictor of hematoma expansion and worse outcomes in patients of spontaneous primary intracerebral hemorrhage (ICH). The biological mechanism of the island sign remains unclear, but its presence might be influenced by the underlying vasculopathy related to Apolipoprotein E (APOE) genotypes. Therefore, we aimed to research the association between APOE genotypes and the island sign.MethodsWe enrolled patients with primary supratentorial ICH in a multicenter cohort in northern China with baseline noncontrast CT images performed within 14 days after symptoms onset and APOE genotype available. The island sign was rated on the CT images according to validated criteria. Univariable and multivariable analyses were used to identify the association between APOE genotypes and the island sign, stratified by the ICH location.ResultsAmong 460 patients enrolled, 122 were lobar ICH. In all patients, after adjusting for age, sex, hypertension, and time to CT, the presence of the APOE ε4 allele (OR 2.020, 95% CI 1.064–3.834, p = 0.032) was associated with the island sign, whereas the presence of the APOE ε2 allele (OR 0.734, 95% CI 0.339–1.593, p = 0.435) was not. After stratifying by ICH location, multivariable analysis revealed that APOE ε4 (OR 3.510, 95% CI 1.393–8.846, p = 0.008), rather than ε2 (OR 0.621, 95% CI 0.203–1.901, p = 0.404), was associated with the island sign in lobar ICH patients. Neither the ε2 nor the ε4 allele was associated with the island sign among nonlobar ICH patients.ConclusionThe APOE ε4 allele was associated with the island sign in lobar ICH patients. Our findings indicate that the presence of the island sign may be influenced by the underlying vasculopathy related to APOE ε4, which increases amyloid deposition in the cerebral vasculature.